The Design Process of Children's Playgrounds Connecting Indoor and Outdoor Spaces: Case of Bornova Children's World, Izmir - Demir, Sara; Turan, Okan; Gunay, Emre (My University, 2021)
The spatial planning and design process are based on the user profiles and their needs. In this context, it is important to know the characteristics of the user groups consisting of children, young people, the elderly and individuals with special needs in terms of healthy and successful design. Therefore, in the design for child users, indoor and outdoor spaces serving the physical, cognitive, and socio-sensory development and based on the principles of colorfulness, mobility and naturalness should be designed. The Children’s World project designed in this context was realized in Bornova district of İzmir province in Turkey. The aim of this study is to design indoor and outdoor playgrounds that reflect the world of children. The children’s playgrounds aim to serve the developmental stages of the child and to be based on the landscape design principles in playgrounds. The landscape design process was implemented step by step for healthy children’s playgrounds. The physical, cognitive, and socio-sensory developmental stages of the children and the colorfulness, mobility and naturalness design criteria of the children’s playgrounds with the flooring materials with playful and colorful patterns, the movable cube game modules and seating units and the plant material that changes color in all seasons were handled within the framework of a holistic design and accordingly, portable and colorful indoor and outdoor playgrounds consisting of exhibition-information-experience areas, workshops and courtyards were created. As a result, in this study which includes original, qualified, functional, innovative and contemporary design solutions, settlement decisions, plan decisions, facade and material decisions, sustainability decisions, and open space decisions were taken. The findings and methodology of this study may serve as an example of the landscape design process for other similar projects to be designed in different regions that take into account the developmental periods and principles of children
Keywords: Mimarlık; Sanat; Kentsel Çalışmalar